Design studies on electronics and data acquisition of a real time diamond spectrometer for the SPARC neutron camera - Petruzzo, M.; Celora, A.; Croci, G.; Gallo, E.; Gorini, G.; Grosso, G.; Nocente, M.; Parisi, M.; Putignano, O.; Raj, P.; Rigamonti, D.; Rebai, M.; et al. (Review of scientific instruments, 2024)
The design of a compact 2 × 2 diamond matrix with independent and redundant pixels optimized for the spectrometric neutron camera of the SPARC tokamak is presented in this article. Such a matrix overcomes the constraints in dynamic range posed by the size of a single diamond sensor while keeping the ability to perform energy spectral analysis, marking a significant advancement in tokamak neutron diagnostics. A charge pre-amplifier based on radio frequency amplifiers based on InGaP technology transistors, offering up to 2 GHz bandwidth with high robustness against radiation, has been developed. A first single-channel device has been tested and proven to provide a fast signal development time of 20–25 ns, necessary to mitigate pileup effects while offering precise energy measurements. As the diamond sensors may suffer from polarization effects due to the trapping of charges at the diamond/metal interface, a periodical bias inversion can guarantee optimal performance. To facilitate that, a reversible high voltage power supply has been developed. The ongoing development of data acquisition equipment and real-time processing algorithms based on programmable gate arrays further enhances the neutron camera’s capabilities.